The Early Labour Market Effects of Generally and Vocationally Oriented Higher Education: Is There a Trade-off? - Dieter Verhaest; Stijn Baert (Institute for the Study of Labor (IZA), 2015)
This study investigates whether the choice for a vocationally versus a generally oriented higher education program entails a trade-off between higher employment chances and better matches at the start of the career (when opting for a vocational orientation) and a lower risk of bad match persistence later on (when opting for a general orientation). We rely on detailed early career spell data of Flemish graduates and assess the vocational orientation of their program by means of the presence of curriculum-based work placement. We model the program choice (vocationally versus generally oriented), the transition to a good match and the preceding transition to a bad match simultaneously. To account for non-random selection into vocational programs and into bad matches, the Timing of Events method is combined with an exclusion restriction. After accounting for unobserved heterogeneity, we do not find any evidence for a trade-off early in the career. This result contributes to the debate about the efficiency of vocationalising tertiary education programs through the implementation of work placement.
Keywords: I21; J24; J64; C21; C41; 330; vocational education; academisation; work placement; mismatch; underemployment; overeducation